Alleviation of Zn toxicity by low water availability - Disante, Karen B; Cortina, Jordi; Vilagrosa, Alberto; Fuentes, David; Hernández, Encarni I; Ljung, Karin (Physiologia Plantarum, 2013)
Heavy metal contamination and drought are expected to increase in large areas worldwide. However, their combined effect on plant performance has been scantly analyzed. This study examines the effect of Zn supply at different water availabilities on morpho-physiological traits of Quercus suber L. in order to analyze the combined effects of both stresses. Seedlings were treated with four levels of zinc from 3 to 150 µM and exposed to low watering (LW) or high watering (HW) frequency in hydroponic culture, using a growth chamber. Under both watering regimes, Zn concentration in leaves and roots increased with Zn increment in nutrient solution. Nevertheless, at the highest Zn doses, Zn tissue concentrations were almost twice in HW than in LW seedlings. Functional traits as leaf photosynthetic rate and root hydraulic conductivity, and morphological traits as root length and root biomass decreased significantly in response to Zn supply. Auxin levels increased with Zn concentrations, suggesting the involvement of this phytohormone in the seedling response to this element. LW seedlings exposed to 150 µM Zn showed higher root length and root biomass than HW seedlings exposed to the same Zn dose. Our results suggest that low water availability could mitigate Zn toxicity by limiting internal accumulation. Morphological traits involved in the response to both stresses probably contributed to this response.
APS
Keywords: Drought; functional traits; Heavy metals; Quercus suber L.

Biosorption of Cr (VI) from water by cork waste - Sfaksi, Z; Azzouz, N; Abdelwahab, A (Arabian Journal of Chemistry, 2013)
The biosorption by cork powder is considered as a promising method for heavy metal removal from industrial waste waters such as chromium tanning factories. The aim of this study is to evaluate the efficiency extent of this method using a cork powder as biosorbent for Cr(VI). The Fourier Transform Infrared spectroscopy (FTIR) analysis permits to distinguish the type of functional groups likely to participate in metal binding. A linear form of BET isotherms for all the three used temperatures (i.e. 25, 35 and 45°C) and a pseudo-second-order equation of adsorption kinetics are obtained. Other experimental results highlight the meaningful influence of parameters such as contact time, pH, concentration of Cr(VI) and the adsorbent particle size on Cr(VI) adsorption . 97% of Cr(VI) has been removed under definite conditions particularly a particle size of diameter d < 0.08 mm and pH of 2-3 values.
Keywords: Biosorption; Cork waste; Cr(VI); Heavy metals; Kinetics

Quercus ilex L. as bioaccumulator for heavy metals in urban areas: Effectiveness of leaf washing with distilled water and considerations on the trees distance from traffic - Ugolini, Francesca; Tognetti, Roberto; Raschi, Antonio; Bacci, Laura (Urban Forestry & Urban Greening, 2013)
In recent years the use of plants as bioaccumulators or bioindicators has increased because enable the prediction of pollution for monitoring purposes, even in urban environments where traffic is a major source of heavy metals pollution. In this study we hypothesized holm oak (Quercus ilex L.) a valid trapping species for heavy metals. We also hypothesized that metals capture capacity by deposition on the crown is connected to the surrounding environmental characteristics and the distance of trees from the source of pollution. The study was conducted in the city of Florence. Holm oaks were selected in different sites near to heavy traffic roads. Concentrations of Zn, Pb, Cd, Cu, Fe, Mn, Cr, and Ba were analyzed through two methods: leaf washing with distilled water and leaf unwashing. One-year-old leaves (new leaves) were also compared with previous-year leaves (old leaves). Our results demonstrated the good capacity of this species to capture heavy metals (Pb, Fe, Mn, Cr, and Ba), particularly due to the presence of old leaves, which enhance the crown deposition surface. Washing was effective and it allowed testing the behaviour with regard to microelements: new leaves showed high Cu concentration, while old leaves had high Pb concentration. The dispersion of metals through the atmosphere was assessed through regression analysis, in two comparable gardens: leaves at farther distance from the traffic were richer in Zn, Pb, Mn, and Ba. The physical context of the surrounding environment was probably altering the distribution of heavy metals as barriers to dispersion, which can reach tens of metres from the source of pollution. Therefore, this work suggests that wind modelling and trees distribution and characteristics should be taken into consideration to evaluate the pollutants dispersion, especially for planning of recreational urban green areas.
The following values have no corresponding Zotero field: publisher: Elsevier GmbH.
Keywords: Deposition; Heavy metals; Holm oak; Internal concentration; Traffic pollution; Urban environment

Quercus ilex L. as bioaccumulator for heavy metals in urban areas: Effectiveness of leaf washing with distilled water and considerations on the trees distance from traffic - Ugolini, Francesca; Tognetti, Roberto; Raschi, Antonio; Bacci, Laura (Urban Forestry & Urban Greening, 2013)
In recent years the use of plants as bioaccumulators or bioindicators has increased because enable the prediction of pollution for monitoring purposes, even in urban environments where traffic is a major source of heavy metals pollution. In this study we hypothesized holm oak (Quercus ilex L.) a valid trapping species for heavy metals. We also hypothesized that metals capture capacity by deposition on the crown is connected to the surrounding environmental characteristics and the distance of trees from the source of pollution. The study was conducted in the city of Florence. Holm oaks were selected in different sites near to heavy traffic roads. Concentrations of Zn, Pb, Cd, Cu, Fe, Mn, Cr, and Ba were analyzed through two methods: leaf washing with distilled water and leaf unwashing. One-year-old leaves (new leaves) were also compared with previous-year leaves (old leaves). Our results demonstrated the good capacity of this species to capture heavy metals (Pb, Fe, Mn, Cr, and Ba), particularly due to the presence of old leaves, which enhance the crown deposition surface. Washing was effective and it allowed testing the behaviour with regard to microelements: new leaves showed high Cu concentration, while old leaves had high Pb concentration. The dispersion of metals through the atmosphere was assessed through regression analysis, in two comparable gardens: leaves at farther distance from the traffic were richer in Zn, Pb, Mn, and Ba. The physical context of the surrounding environment was probably altering the distribution of heavy metals as barriers to dispersion, which can reach tens of metres from the source of pollution. Therefore, this work suggests that wind modelling and trees distribution and characteristics should be taken into consideration to evaluate the pollutants dispersion, especially for planning of recreational urban green areas.
Keywords: Deposition; Heavy metals; Holm oak; Internal concentration; Traffic pollution; Urban environment

Use of cork powder and granules for the adsorption of pollutants: a review. - Pintor, Ariana M A; Ferreira, Catarina I A; Pereira, Joana C; Correia, Patrícia; Silva, Susana P; Vilar, Vítor J P; Botelho, Cidália M S; Boaventura, Rui A R (Water research, 2012)
Cork powder and granules are the major subproducts of the cork industry, one of the leading economic activities in Portugal and other Mediterranean countries. Many applications have been envisaged for this product, from cork stoppers passing through the incorporation in agglomerates and briquettes to the use as an adsorbent in the treatment of gaseous emissions, waters and wastewaters. This paper aims at reviewing the state of the art on the properties of cork and cork powder and their application in adsorption technologies. Cork biomass has been used on its original form as biosorbent for heavy metals and oils, and is also a precursor of activated carbons for the removal of emerging organic pollutants in water and VOCs in the gas phase. Through this literature review, different potential lines of research not yet explored can be more easily identified.
Keywords: activated carbon; Adsorption; Cork granules; cork powder; Heavy metals; Pollutants

Nutrients and trace elements content of wood decay fungi isolated from oak (Quercus ilex). - Campos, Juan a (Biological trace element research, 2011)
The presence of chemical elements and the differences in their concentration in the fruiting bodies of wood decay fungi may reflect their activity either as saprobes or parasites and the intimate physiological relation with the substrate from which they extract their nutrients. In order to test this hypothesis, we carried out a systematic sampling of eight species of wood decay fungi on oak (Quercus ilex). The data show that the concentration of some elements exhibits a very wide range of values for the species tested, which could mean that the relative content of some elements may provide clues about the nature of the substrate and, moreover, about the nutritional physiology. The comparison between the foliar analysis (FA) and the elemental content of fungi may shed light on the specific physiological behaviour of the species. Potassium is an element accumulated in fungal biomass in higher quantities than in the FA. By contrast, calcium appears in foliar analysis in much higher quantities than in fungal fruiting bodies' biomass. Concerning this element, we have also found profound differences between the two species phylogenetic groups and lifestyle. Of all elements measured, we believe that the relative accumulation of K and Ca may be related to the close connection between fungi and the substrate on which they live and may also explain their physiological role as saprobes or parasites. When the lifestyle and the systematic position of the different species sampled were compared, differences also emerged in the content of Na and Ca.
The following values have no corresponding Zotero field: accession-num: 21748305
Keywords: Epiphytic fungi; Heavy metals; Nutrients; Nutrition physiology; Saprobe fungi; Trace Elements

Afforestation of a trace-element polluted area in SW Spain: woody plant performance and trace element accumulation - Domínguez, Maria Teresa; Madejón, Paula; Marañón, Teodoro; Murillo, José Manuel (European Journal of Forest Research, 2008)
Trace element soil pollution can have ecotoxic eVects on plants, which could negatively aVect the restoration of a degraded area. In this work, we studied the revegetation success in diVerent sites within a trace elementpolluted area (Guadiamar River Valley, SW Spain). We analysed the survival and growth patterns of aVorested plants of seven Mediterranean woody species, and their relation to soil pollution, over 3 years. We also analysed the trace element accumulation in the leaves of these species. The area was polluted mainly by As, Cd, Cu, Pb and Zn (soil total concentrations up to 250, 3.6, 236, 385 and 510 mg kg ¡1 , respectively). The woody plant performance was very diVerent between sites and between species; in the riparian sites, plant survival rates were nearly 100%, while in the upland terrace sites species such as Quercus ilex and Ceratonia siliqua showed the lowest survival rates (less than 30%) and also the lowest relative growth rates. There were no signiWcant relationships between plant performance and soil pollution in the riparian sites, while in the upland sites mortality, but not growth, was related to soil pollution, although that could be an indirect eVect of diVerent substrate alteration between sites. The accumulation of soil pollutants in the studied plants was low, with the exception of Salicaceae species, which accumulated Cd and Zn in the leaves above 1 and 200 mg kg ¡1 , respectively. We discuss the results with regard to the aVorestation of trace-element polluted areas.
Keywords: Heavy metals; mediterranean woody species; plant survival; relative growth rates; soil remediation

Afforestation of a trace-element polluted area in SW Spain: woody plant performance and trace element accumulation - Domínguez, Maria Teresa; Madejón, Paula; Marañón, Teodoro; Murillo, José Manuel (European Journal of Forest Research, 2008)
Trace element soil pollution can have ecotoxic eVects on plants, which could negatively aVect the restoration of a degraded area. In this work, we studied the revegetation success in diVerent sites within a trace elementpolluted area (Guadiamar River Valley, SW Spain). We analysed the survival and growth patterns of aVorested plants of seven Mediterranean woody species, and their relation to soil pollution, over 3 years. We also analysed the trace element accumulation in the leaves of these species. The area was polluted mainly by As, Cd, Cu, Pb and Zn (soil total concentrations up to 250, 3.6, 236, 385 and 510 mg kg ¡1 , respectively). The woody plant performance was very diVerent between sites and between species; in the riparian sites, plant survival rates were nearly 100%, while in the upland terrace sites species such as Quercus ilex and Ceratonia siliqua showed the lowest survival rates (less than 30%) and also the lowest relative growth rates. There were no signiWcant relationships between plant performance and soil pollution in the riparian sites, while in the upland sites mortality, but not growth, was related to soil pollution, although that could be an indirect eVect of diVerent substrate alteration between sites. The accumulation of soil pollutants in the studied plants was low, with the exception of Salicaceae species, which accumulated Cd and Zn in the leaves above 1 and 200 mg kg ¡1 , respectively. We discuss the results with regard to the aVorestation of trace-element polluted areas.
Keywords: Heavy metals; mediterranean woody species; plant survival; relative growth rates; soil remediation

Plant MTs-long neglected members of the metallothionein superfamily - Freisinger, Eva (DALTON TRANSACTIONS, 2008)
Occurrence of metallothioneins (MTs) was initially thought to be restricted to the animal kingdom, and the corresponding functions such as detoxification of heavy metal ions were assumed to be taken over in plants by the enzymatically synthesized phytochelatins. This perception was revised in the past years, and the existence of plant metallothioneins is generally accepted. Compared to the vertebrate forms, members of the plant MT family display a significantly larger sequence diversity, however, surprisingly little information is available concerning their possible functions, properties, and structures. Gene expression studies, and thus studies on the mRNA level, are the major source of data aiming at elucidating the function of plant MTs. However, so far it is not possible to unambiguously assign a specific function to a given metallothionein as proposed functions overlap, are complementary to each other, or even contradictory results are obtained. With respect to the structures and properties of plant metallothioneins even less scientific contributions are available illustrating the early stages, in which this research area resides. Existing data covers the metal ion content of the different plant metallothionein species and the pH stabilities of the resulting metal-thiolate clusters. Further, for a limited selection of proteins the number of clusters formed has been proposed and predictions towards the secondary structure of the protein backbone made. A recently determined three-dimensional structure of the larger domain of the wheat metallothionein E(c)-1 describes a metal ion coordination mode unprecedented for any metallothionein so far.
APS
Keywords: Heavy metals; plant metallothioneins

Plant MTs-long neglected members of the metallothionein superfamily - Freisinger, Eva (DALTON TRANSACTIONS, 2008)
Occurrence of metallothioneins (MTs) was initially thought to be restricted to the animal kingdom, and the corresponding functions such as detoxification of heavy metal ions were assumed to be taken over in plants by the enzymatically synthesized phytochelatins. This perception was revised in the past years, and the existence of plant metallothioneins is generally accepted. Compared to the vertebrate forms, members of the plant MT family display a significantly larger sequence diversity, however, surprisingly little information is available concerning their possible functions, properties, and structures. Gene expression studies, and thus studies on the mRNA level, are the major source of data aiming at elucidating the function of plant MTs. However, so far it is not possible to unambiguously assign a specific function to a given metallothionein as proposed functions overlap, are complementary to each other, or even contradictory results are obtained. With respect to the structures and properties of plant metallothioneins even less scientific contributions are available illustrating the early stages, in which this research area resides. Existing data covers the metal ion content of the different plant metallothionein species and the pH stabilities of the resulting metal-thiolate clusters. Further, for a limited selection of proteins the number of clusters formed has been proposed and predictions towards the secondary structure of the protein backbone made. A recently determined three-dimensional structure of the larger domain of the wheat metallothionein E(c)-1 describes a metal ion coordination mode unprecedented for any metallothionein so far.
APSAPSThe following values have no corresponding Zotero field: pub-location: THOMAS GRAHAM HOUSE, SCIENCE PARK, MILTON RD, CAMBRIDGE CB4 0WF, CAMBS, ENGLAND publisher: ROYAL SOC CHEMISTRY
Keywords: Heavy metals; plant metallothioneins

UTILIZACION DE ESPECIES AUTOCTONAS PARA RECUPERACION DE SUELOS DEGRADADOS ENMENDADOS CON LODOS RESIDUALES - GASCÓ, G.; ALONSO, J.; MARTINEZ IÑIGO, M. J.; LOBO, M. C. (III Congreso Forestal Español, 2001)
The objective of this study was to analyse if composted sewage sludges could be used to amend degraded soils. Two different treatments were applied to Nerium oleander L. and Quercus ilex L (120 Tons/Ha. y 60 Tons/Ha) in a greenhouse with controled conditions. Both heavy metals and nutrients soil contents were analysed to study the influence of the compost in soil properties. Moreover, the effect of the residue in physiological and nutritive plants properties were evaluated.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español pub-location: Granada
Keywords: composted sewage sludge; degraded soils; Heavy metals; Nerium oleander L.; Quercus ilex L.

UTILIZACION DE ESPECIES AUTOCTONAS PARA RECUPERACION DE SUELOS DEGRADADOS ENMENDADOS CON LODOS RESIDUALES - GASCÓ, G; ALONSO, J; MARTINEZ IÑIGO, M J; LOBO, M C (III Congreso Forestal Español, 2001)
The objective of this study was to analyse if composted sewage sludges could be used to amend degraded soils. Two different treatments were applied to Nerium oleander L. and Quercus ilex L (120 Tons/Ha. y 60 Tons/Ha) in a greenhouse with controled conditions. Both heavy metals and nutrients soil contents were analysed to study the influence of the compost in soil properties. Moreover, the effect of the residue in physiological and nutritive plants properties were evaluated.
Keywords: composted sewage sludge; degraded soils; Heavy metals; Nerium oleander L.; Quercus ilex L.

Dendroanalysis: a tool for biomonitoring environmental pollution? - Nabais, C; Freitas, H; Hagemeyer, J (The Science of the total environment, 1999)
Trees of temperate regions usually form visible annual growth rings, which can be dated accurately. It is therefore possible to collect wood samples of different age and analyse their heavy metals content in order to get a chronological record of trace elements pollution in the tree's environment. This method of retrospective biomonitoring was called dendroanalysis. A basic assumption of dendroanalysis is the stability of the mineral distribution patterns, i.e. once the elements are stored, no significant mobility should occur. Additionally, neighbouring trees growing in the same environment should show similar radial element patterns. While some studies presented good correlations between radial distributions of heavy metals in tree rings and temporal records of pollution from industry or traffic, others failed in using dendroanalysis as a chronological record of pollution. Probably some elements can move at a certain rate in radial direction through the ray parenchyma cells. In this way the radial element distributions are subsequently changed. Growth rates of tree rings can also influence the concentrations of elements in wood. During periods of slow growth higher concentrations of elements can be found in the wood. Therefore, radial distribution patterns of heavy metals in tree rings should be used with caution as a tool for retrospective biomonitoring of environmental pollution.
Keywords: biomonitoring; Dendroanalysis; Heavy metals

Heavy Metals in Moss and Bark From Urban Area of Florence: A New Cleaness Procedure for Removing Superficial Particulate Matter - Ducceschi, L; Legittimo, P Cellini; Bonzi, L Morassi (Chemistry and Ecology, 1999)
Abstract Hypnum cupressiforme epiphytic moss and tree bark (elm and holm oak) samples have been collected in three sites of the city of Florence in the period 1995?1998. Lead, zinc, copper, and cadmium were determined by differential pulse anodic stripping voltammetry (DPASV) in about 200 samples collected at different heights above ground. A new clean-up procedure by nitrogen jet has been followed and its efficiency has been also verified by electron microscopy (SEM and ESEM techniques). Lead median contents in moss and bark samples fall within the ranges of 0.052?0.86 and 0.20?1.30 ?moles g?1 (dry weight), resulting values for moss and bark are proportional to the vehicular traffic density. the increasing use of lead-free gasoline has not been followed by a decrease of lead moss concentration.
doi: 10.1080/02757549908037642
Keywords: Bark; biomonitoring; environmental scanning electron microscopy (ESEM); Heavy metals; Moss

Heavy Metals in Moss and Bark From Urban Area of Florence: A New Cleaness Procedure for Removing Superficial Particulate Matter - Ducceschi, L.; Legittimo, P. Cellini; Bonzi, L. Morassi (Chemistry and Ecology, 1999)
Abstract Hypnum cupressiforme epiphytic moss and tree bark (elm and holm oak) samples have been collected in three sites of the city of Florence in the period 1995?1998. Lead, zinc, copper, and cadmium were determined by differential pulse anodic stripping voltammetry (DPASV) in about 200 samples collected at different heights above ground. A new clean-up procedure by nitrogen jet has been followed and its efficiency has been also verified by electron microscopy (SEM and ESEM techniques). Lead median contents in moss and bark samples fall within the ranges of 0.052?0.86 and 0.20?1.30 ?moles g?1 (dry weight), resulting values for moss and bark are proportional to the vehicular traffic density. the increasing use of lead-free gasoline has not been followed by a decrease of lead moss concentration.
doi: 10.1080/02757549908037642doi: 10.1080/02757549908037642The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Bark; biomonitoring; environmental scanning electron microscopy (ESEM); Heavy metals; Moss

Effects of urban heavy metal pollution on organic matter decomposition in Quercus ilex L. Woods - Cotrufo, M. F.; Santo, A. V. De; Alfani, Anna (Environmental Pollution, 1995)
Decomposition of oak (Quercus ilex) leaves containing different concentrations of Fe, Zn, Cu, Cr, Ni and Pb was measured in laboratory microcosms. The leaves were collected from a polluted site inside the city of Naples and from a control site away from the city. Soil was sampled from the upper A horizon (0-5 cm) at both sites and analyzed for respiration, microbial biomass and abundance of fungal mycelia. The soils from the two sites differed significantly in heavy metals concentrations. The accumulated mass loss reached an asymptotic value after four months both for the control and polluted litters. However, control and polluted litters significantly differed in accumulated mass loss, that was respectively 40 % and 29 % of the initial weight, after 10 months. Moreover decomposition rates appeared to be strongly influenced by metal contamination in the early stages, while in later stages, they did not differ significantly. Litter respiration appeared to be inhibited by metal contamination and showed pattern and rates consistent with those found for litter decomposition. Fungal mycelia were significantly less abundant both in litter and soil from the polluted site than from the con- trol site. Metabolic activity (both as soil respiration and degree of mineralization) was lower in the polluted soil. Soil respiration and amount of soil mycelia correlated negatively with soil Pb, Zn and Cr concentration.
Keywords: Fungal biomass (voyant9; Heavy metals; litter decomposition; pollution; Soil microbial biomass; Soil respiration

Plant species as indicators of geochemical anomalies: Experiences onIlex aquifolium (holly) - Legittimo, P. Cellini; Ducceschi, L.; Martini, M. (Environmental Geology, 1995)
The distribution of Zn, Cd, Pb, and Cu, in plants growing in mineralized and sterile areas of Tuscany has been studied to verify if and to what extent metal- accumulating species represent evidence of geochemical anomalies in soils. Samples of leaves and twigs from trees were collected, and analyzed by means of differential pulse anodic stripping voltammetry (DPASV). Hollies, bram- bles, and Holm oaks in particular were considered in the mineralized area of Bottino, and the special aptitude of hollies in concentrating Cd with respect to the other metals has been verified. Cadmium has been previously recog- nized as a pathfinder for zinc ore bodies; the results of this investigation appear to point out the relevance of holly as a bioindicator of geochemical zinc anomalies. Lower metal concentration characterizes the same species from other mineralized and sterile zones, with the exception of the urbanized area of Florence, where relatively higher Zn concentrations in hollies appear to be due to atmospheric pollution.
Keywords: biogeochemical prospecting; Heavy metals; Plants

Plant species as indicators of geochemical anomalies: Experiences onIlex aquifolium (holly) - Legittimo, P Cellini; Ducceschi, L; Martini, M (Environmental Geology, 1995)
The distribution of Zn, Cd, Pb, and Cu, in plants growing in mineralized and sterile areas of Tuscany has been studied to verify if and to what extent metal- accumulating species represent evidence of geochemical anomalies in soils. Samples of leaves and twigs from trees were collected, and analyzed by means of differential pulse anodic stripping voltammetry (DPASV). Hollies, bram- bles, and Holm oaks in particular were considered in the mineralized area of Bottino, and the special aptitude of hollies in concentrating Cd with respect to the other metals has been verified. Cadmium has been previously recog- nized as a pathfinder for zinc ore bodies; the results of this investigation appear to point out the relevance of holly as a bioindicator of geochemical zinc anomalies. Lower metal concentration characterizes the same species from other mineralized and sterile zones, with the exception of the urbanized area of Florence, where relatively higher Zn concentrations in hollies appear to be due to atmospheric pollution.
Keywords: biogeochemical prospecting; Heavy metals; Plants